Real Time Cascade PI Control for Position Monitoring of DC Brushed Motor - Ibrahim , Mazree; Kamarudin, Muhammad Nizam; Syed Najib , Syed Salim; Aminurrashid , Noordin (WASET, 2009)
This paper depicts the development of real time motor drive system. The modeling of Direct Current (DC) motor is vital in this work and hence is discussed in brief. Experimental setup consists of DC motor, rotary encoder, interface card and personal computer is thoroughly configured to obtain useful data such as control signal, speed and position of the motor. User interface and control algorithm is developed using Microsoft Visual C#. Proportional-Integral (PI) algorithm is developed to perform cascaded control of the DC motor. The system equipped with fixed inner current loop control parameters while the outer speed and position loop is varied to obtain the most satisfied position and speed of such motor. Through comparison of demanded speed and position, literal analysis of real time speed and position is thoroughly discussed.